Proportional Thinking Characteristics of Students In Solving Direct Proportion Problems in Junior High School - Lanani, Karman; Nur, Isman Muhammad; Sari, Diah Prawitha (Universitas Islam Negeri Raden Intan Lampung, 2024)
One of the most common obstacles students face when solving proportion problems is their tendency to use the addition concept rather than the multiplication concept. This study aims to analyze and characterize the proportional thinking characteristics of students who solve direct proportion problems. The research employs a qualitative, exploratory-descriptive methodology. The subjects were three eighth-grade students. Data was collected in two stages using supplementary instruments, including direct proportion questions and interviews. In the initial stage, students answered questions orally while researchers observed their activities and took notes, which were confirmed during interviews. In the second stage, task-based interviews were used to investigate the students' proportional thinking processes. Data analysis involved examining the students' work and interview transcripts, which were then coded to identify noteworthy findings. The study identified three characteristics of proportional thinking: (1) additive different thinking; (2) multiplication continuation thinking; and (3) multiplication proximity thinking. The foundation for solving direct proportion problems lies in students' understanding of the relationship between two quantities in a ratio. Teachers should prioritize the explicit disclosure of students' cognitive processes related to the subject matter. Additional studies are recommended to further investigate students' cognitive processes.